MENINGKATKAN KEMAMPUAN SPEAKING MELALUI TEKNIK DRAMA DI JAMPANG ENGLISH VILLAGE BOGOR - Yan Ardian Subhan; Eka Margianti Sagimin; Kamil Falahi; Wiwit Sariasih; Afrianti Wulandari (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2021)
This Community Service Activities (PKM) in Madina Zone, Jampang English Village, Jampang Bogor aims to improve students' speaking ability in English in public. This PKM uses English speaking training methods using Drama training medium by involving 30 respondents from the elementary or junior high school students who are from several elementary to junior high school students scattered in the Madina JEV Zone area. From the results of this PKM activity it was found that the English language training method with a mentoring approach, technical training in role playing and the practice of drama entitled